Flexible layout design for the battery cell manufacturing industry to optimize for the unknown future - Axelsson, Pontus; Jansson, Maja (My University, 2024)
The worlds transition towards a more sustainable society is a driver for the demand in electrical batteries for vehicles. To be able to meet the demand new battery cell factories needs to be build, and start their production as fast as possible. This master thesis has therefore investigated how the factory layout design can increase its flexibility by using different project models as a basis. The results shows that the flexibility can be increased, but the investment cost is in most of the cases higher than if flexibility in the layout is disregarded. The highest level of flexibility would be reached with help of the agile methodology where the generated layout is based on smaller modules. The set-based method could lead to an increase in flexibility depending on the scenario, but has several other advantages. The waterfall methodology would on the other hand not increase the flexibility of the layouts if not re-configurable manufacturing systems (RMS) are included. Therefore the battery cell manufacturers needs to make a choice between saving investment cost and instead face the risk of re-layout costs or if they want to create a flexible factory that can change its production together with the changing customer demands.
Keywords: Battery Cell; Factory Layout; Project Models; Flexibility; Production Processes; Li-Ion battery